What can laughter and clowning do against what kills (us)? (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
The article initially addresses death as the theme of clown shows performed by the author and clown in her doctoral research, within a perspective intertwined with Nietzsche's tragic thought in the affirmation of life. Faced with the worsening of the health and social crisis that erupted in the COVID-19 pandemic in the country, the confrontation of death through comic and clown poetics comes to be considered from new angles and questions by the author, in view of the of the ostentatious and dominant necropolitics (Mbembe, 2016) of the far-right government in the presidency of Brazil in the period. From this context, some questions are posed about artistic creation, such us how to face what kills (us), saddens and oppresses (us), through play and creation of humor in clown art in favor of life.
Keywords: Clown art; Death; Laughter; Affirmation of life